Bioceramics, Bioglasses and Gels for Tissue Engineering (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Biomaterials engineering is a dynamic and rapidly evolving field that plays a pivotal role in advancing medical technology, improving patient care, and addressing healthcare challenges. Advancements in interdisciplinary fields such as chemistry, physics, material science, nanotechnology, manufacturing technology, and bioengineering have the opportunity to significantly impact patient lives by developing innovative solutions, thereby improving the performance and safety of medical devices and therapies. This Special Issue mainly aims to present the recent development of advanced biomaterials such as gels, ceramics, and glasses for healthcare applications, including hard and soft tissue engineering, medical implants, drug delivery systems, and more. This Special Issue, made up of 4 reviews and 8 original articles, represents the keen and diverse research ensuing toward innovative functionalities and their incorporation with cutting-edge fabrication techniques. It will also focus on the chemistry of biomaterials and their characteristics, such as bioactivity, biocompatibility, and biodegradation, and how their chemical–physical properties (such as porosity, morphology, mechanical strength, etc.) can influence cells and living systems.